1998
DOI: 10.1021/jp972635z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Conformation in Oligo(ethylene glycol)-Terminated Self-Assembled Monolayers on Gold and Silver Surfaces Determines Their Ability To Resist Protein Adsorption

Abstract: We report data from infrared absorption (FTIR) and X-ray photoelectron spectroscopies that correlate the molecular conformation of oligo(ethylene glycol) (OEG)-terminated self-assembled alkanethiolate monolayers (SAMs) with the ability of these films to resist protein adsorption. We studied three different SAMs of alkanethiolates on both evaporated Au and Ag surfaces. The SAMs were formed from substituted 1-undecanethiols with either a hydroxyl-terminated hexa(ethylene glycol) (EG6-OH) or a methoxy-terminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

123
1,536
4
8

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,222 publications
(1,686 citation statements)
references
References 50 publications
123
1,536
4
8
Order By: Relevance
“…Since the thiol groups are located at the gold-monolayer interface, the lower sulfur concentrations are due to the attenuation of sulfur photoelectrons by overlying organic layers. 15,18,47 NTA a and NTA b were exposed to OEG diluent thiol for 0.5 hr to 48 hr. Composition trends observed suggests that the OEG thiol diluent produced different results for NTA a and NTA b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the thiol groups are located at the gold-monolayer interface, the lower sulfur concentrations are due to the attenuation of sulfur photoelectrons by overlying organic layers. 15,18,47 NTA a and NTA b were exposed to OEG diluent thiol for 0.5 hr to 48 hr. Composition trends observed suggests that the OEG thiol diluent produced different results for NTA a and NTA b.…”
Section: Resultsmentioning
confidence: 99%
“…The NTA concentration in the NTA b monolayer is calculated by the degree of attenuation of the substrate Au 4f XPS signal. 18,29 Surface NTA concentrations were significantly affected by the self-assembly conditions of the NTA and OEG thiols. Maximum NTA concentration was observed to be 1.9 headgroup/ nm 2 in NTA a assembled for 24 hr, while a lower concentration was observed in NTA b assembled for 5 min.…”
Section: Resultsmentioning
confidence: 99%
“…It is, however, clear through recent systematic experimental work and earlier experimental documentation that certain hydrophilic surfaces are quite protein resistant (5,(9)(10)(11)(40)(41)(42). Consequently, the bonding and structure of water at the surfaces, with which proteins interact, are important.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid films at interfaces have actually previously been shown to be quite efficient in preventing protein adsorption (4-7), and have also been shown to limit cell attachment (8) (a fact that can probably be directly related to the low affinity to protein adsorption on the membrane; if proteins do not bind, cells will not find attachment sites). The actual mechanisms behind the protein resistance are, however, still poorly understood, although recent important experimental data have addressed, e.g., the role of the polarity of functional groups (9) interacting with proteins, surface wettability (10), and the role of the hydration layer of the protein-resistant surfaces (11). Recently the influence of surface polarizability and surface hydration layer thickness on the protein adsorption energetics was treated theoretically (12).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hydrophobic proteins have been suggested to be able to adsorb to PEObrushes through their hydrophobic moieties (Furness et al, 1998), which was confirmed by the work of Sheth et al (2000), demonstrating attraction of PEO to non-polar surfaces. It has furthermore been shown that PEO can exist in a protein-repulsive, polar, helical or random structure, and a protein-attractive, apolar, all-trans structure (Harder et al, 1998;Currie et al, 2003). The work of Efremova et al (2001) showed that changing circumstances, such as temperature or compressive load, can change PEO from a protein-repellent to a protein-attractive state.…”
Section: Discussionmentioning
confidence: 99%